Application of Robotics in Large-Scale Agriculture in Australia - Loso Judijanto; Haruto Takahashi; Yui Nakamura (Techno Agriculturae Studium of Research, 2024)
Large-scale agriculture in Australia faces various challenges, such as labor shortages, land management efficiency, and suboptimal use of resources. Robotic technology offers innovative solutions to address these problems by automating agricultural processes, such as planting, fertilizing, and harvesting. This study aims to evaluate the impact of the application of robotics technology in large-scale agriculture in Australia, including its impact on productivity, resource use efficiency, and environmental sustainability. The research uses a combined qualitative and quantitative approach. Quantitative data was collected through surveys of farmers in different regions of Australia, while qualitative data was obtained from in-depth interviews with farmers and agronomists. The data collected was analyzed to understand the impact of robotics technology on productivity and resource use. The results show that the use of robotic technology increases productivity by 20% in the wheat and cotton sectors. In addition, the use of sensor-based automated irrigation systems reduces water consumption by up to 30%, while drones for pesticide applications help reduce chemical use by up to 25%. Robotics technology has contributed significantly to improving the efficiency of large-scale agriculture in Australia, both in terms of increasing crop yields and reducing resource use. These findings suggest that robotics can be a sustainable solution for modern agriculture, although more research is needed to evaluate its long-term impact on the environment.